ANALISIS IMPLEMENTASI KEBIJAKAN PERATURAN WALIKOTA KOTA MANADO, NO. 33 TAHUN 2018, TENTANG PENGURANGAN DAN PENANGANAN SAMPAH BERBASIS KECAMATAN DI KOTA MANADO - Maramis, Regina Urai; Tampongangoy, Deysi Livy Natalia; Lasut, Markus T. (AGRI-SOSIOEKONOMI, 2022)
This study aims to analyze the policy implementation of waste management current (while do) in the City of Manado, namely the R`egulation of the Mayor of the City of Manado, the Number 33 in 2018, about the Reduction and Handling of Waste-Based District of the City of Manado. This research uses a qualitative method. The results showed that the Implementation of the Policy Rule Mayor of the City of Manado, the Number 33 in 2018, about the Reduction and Handling of Waste-Based District of the City of Manado has not been well can be seen the delivery of socialization is not a row as well as explain the procedure and stages of waste management to the community and is still limited to ceremonial activities that could not yet reach out to the community as a whole furthermore resource in the implementation of policies for handling and waste reduction already exist however between the amount of the janitor and the available infrastructure is still not enough when compared with the work load this is also related to the lack of the number of the budget for waste management in the City of Manado. In conclusion the process of handling and waste reduction should not be limited by the time of the bureaucratic work, need to be revised Regulations Mayor of the City of Manado NO.The 33-Year 2018 on the reduction and handling of waste-based district, relating to the authority or delegation of tasks that has been given to the district should have pulled back and formed a special body responsible for waste management in the City of Manado also including human resources, budget and infrastructure needed to be managed a specialized agency of the.